Characterization of Lung Cancer: A 10-Year Experience from a Tertiary Hospital in Yaounde, Cameroon - Bell, MD, Esther Mbassi Dina; Ndom, MD, Paul; Eloundou, MD, Albertine; Um, MD, Germaine; Orock, MD, George Enow; Doh, MD, Anderson; Huo, MD, PhD, Dezheng (North American Journal of Medicine and Science, 2010)
The incidence rate of lung cancer in Africa is low. However, there are few studies reporting clinical characteristics of lung cancer in African countries. We did a study of lung cancer at the Medical Oncology Service of the Yaounde General Hospital, Cameroon, from January 1998 to December 2007. Out of the 2,355 cancer patients seen at this hospital over a 10-year period, 48 patients (28 men and 20 women) were diagnosed with lung cancer. The average age (SD) of patients was 53 (13) years and ranged from 25 to 80 years. Seven patients were cigarette smokers. The median duration from initial symptoms to visiting doctors was 5 months (interquartile range: 3-11 months). The most common histology types were squamous cell carcinomas (31, 65%), followed by adenocarcinomas (8, 17%), large cell carcinomas (4, 8%), small cell carcinomas (4, 8%), and fibrosarcoma (1, 2%). Of the 19 patients with stage classification, 8 had stage IV and 11 had stage III disease. Only 14 patients reported having received treatment, including chemotherapy, radiotherapy, and/or surgery. In conclusion, lung cancer was uncommon in Yaounde, Cameroon, but most of patients presented with advanced stage due to long delay in seeking diagnosis. Less than half of the patients received chemotherapy, radiotherapy, or surgery.